Effects of inter element spacing on large antenna array characteristics - Muhamad Adnan, Noor Hidayah; Islam, Md. Rafiqul; Alam, A. H. M. Zahirul (Institute of Electrical and Electronics Engineers Inc., 2018)
Large-scale antenna arrays have been the current interest in the study of massive MIMO as a promising technology for 5G. Planar arrays have become the suitable antenna array configurations for massive MIMO since they provide directive beams. In this paper, planar array is proposed with square and rectangular arrangements based on 2 x 2 antenna elements as one subarray. Then, array factor (AF) for the planar array based on the subarray with up to 64 antenna elements is calculated to analyze the effects of inter element spacing on large antenna array characteristics. It is observed that large number of antenna elements contribute to large number of side lobes in the AF pattern and higher directivity at the expense of narrower HPBW. Inter element spacing less than 0.5λ produces lower directivity and higher HPBW. Therefore, inter element spacing equal or larger than 0.5λ is suitable to achieve higher directivity for large antenna array applications.